Laser speckle contrast imaging for quantitative assessment of facial flushing during mesenteric traction syndrome in upper gastrointestinal surgery. - Ring, Linea L.; Strandby, Rune B.; Henriksen, Amalie; Ambrus, Rikard; Sørensen, Henrik; Gøtze, Jens P.; Svendsen, Lars B.; Achiam, Michael P. (Journal of Clinical Monitoring & Computing, 2019)
The mesenteric traction syndrome (MTS) is associated with prostacyclin (PGI2) facilitated systemic vasodilatation during surgery and is identified by facial flushing. We hypothesized that severe facial flushing would be related to the highest concentrations of plasma PGI2 and accordingly to the highest levels of skin blood flow measured by laser speckle contrast imaging (LSCI). Patients scheduled for major upper abdominal surgery were consecutively included. Within the first hour of the procedure, facial flushing was scored according to a standardized scale, and skin blood flow (LSPU) was continuously measured on the forehead and the cheeks by LSCI. Arterial blood samples for 6-keto-PGF1α (stable metabolite of PGI2) and hemodynamic variables were obtained at defined time points. Overall, 66 patients were included. After 15 min of surgery, patients with severe flushing demonstrated the highest plasma 6-keto-PGF1α concentration and the most significant decrease in systemic vascular resistance. Accordingly, the skin blood flow on the forehead (238 [201-372] to 562 LSPU [433-729]) and the cheeks (341 [239-355] to 624 LSPU [468-917]) increased and were significantly higher than for patients with moderate or no flushing (both, P = 0.04). A cut-off value for skin blood flow could be defined for both the cheeks and the forehead for patients with severe flushing vs. no flushing (425/456 LSPU, sensitivity 75/76% and specificity 80/85%). MTS is linked to an increase in facial skin blood flow during upper gastrointestinal surgery. By applying LSCI, it is possible to quantitatively register facial blood flow, and thereby provide an objective tool for intraoperative verification of MTS.